Diagnosis and treatment of the irritable bowel syndrome: clinical guidelines of the Russian gastroenterological association and Russian association of coloproctology - V. T. Ivashkin; Yu. A. Shelygin; Ye. K. Baranskaya; Ye. A. Belousova; A. G. Beniashvili; S. V. Vasilyev; A. O. Golovenko; O. V. Golovenko; Ye. G. Grigoryev; N. V. Kostenko; T. L. Lapina; I. D. Loranskaya; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of publication. To present recent RGA evidencebased medicine centered guidelines on diagnosis, rational pharmacotherapy and management of irritable bowel syndrome (IBS). Summary. IBS - is a functional bowel disorder is manifested by recurrent abdominal pain that develops at least once per week and characterized by at least two of the following signs: it is related to bowel movements, associated to the change in stool frequency and/ or shape. These symptoms should be present in the patient for the last 3 months at overall duration of observation for six months or more. Similar to other functional gastrointestinal disorders, the diagnosis of IBS can be established at compliance of symptoms to Rome IV criteria and the absence of organic gastrointestinal diseases that could cause patient’s symptoms. Due to complexity of differential diagnostics, IBS should be considered as diagnosis by exclusion that require following investigations: clinical and biochemical blood tests; IgA or IgG anti-tissue transglutaminase antibodies; thyroid hormone levels; fecal occult blood test; glucose or lactulose hydrogen breath test for bacterial overgrowth syndrome; stool test for coliform bacteria, stool test for Clostridium difficile toxins A and B; fecal calprotectin level; abdominal ultrasound; upper and lower endoscopies, at indications - with biopsies. IBS treatment requires diet and lifestyle modifications, intake of pharmacological agents and psychotherapy. Antispasmodic medications (e.g.: hyoscine butylbromide, pinaverium bromide, mebeverine) are recommended for abdominal pain relief. For diarrhea-predominant IBS such medications as loperamide hydrochloride, dioctaedric smectite, non-absorbable antibiotic rifaximin and probiotics may be prescribed. For treatment of IBS with constipation use of bulking agents (psyllium), osmotic laxatives (macrogol 4000, lactulose), laxatives stimulating intestinal motility (bisacodyl) may be applied. Enterokinetic agent prucalopride may be prescribed at inefficacy of laxatives. Peripheral opioid agonists (trimebutine maleate) normalizing intestinal motor activity via action on different subtypes of peripheral opioid receptors, combined plant-derived medication STW 5 are applied as well. Conclusion. Implementation of clinical guidelines can determine timely diagnosis and treatment of various IBS types. The IBS is characterized by scalloping course with relapse periods that are provoked by psychoemotional stress and remissions. The risk of organic bowel diseases IBS patients is not higher, than in total population.